2005
DOI: 10.1093/deafed/eni006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Writing of Deaf College Students: Reevaluating a Direct Assessment of Writing

Abstract: The NTID Writing Test was developed to assess the writing ability of postsecondary deaf students entering the National Technical Institute for the Deaf and to determine their appropriate placement into developmental writing courses. While previous research (Albertini et al., 1986; Albertini et al., 1996; Bochner, Albertini, Samar, & Metz, 1992) has shown the test to be reliable between multiple test raters and as a valid measure of writing ability for placement into these courses, changes in curriculum and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Both the original written version and the typed version were sent to experienced raters who were faculty members in the English department at the National Technical Institute for the Deaf (NTID) for scoring. The scoring procedure was developed for assessing the writing ability of postsecondary deaf students (Schley & Albertini, 2005). Each essay was evaluated by three raters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the original written version and the typed version were sent to experienced raters who were faculty members in the English department at the National Technical Institute for the Deaf (NTID) for scoring. The scoring procedure was developed for assessing the writing ability of postsecondary deaf students (Schley & Albertini, 2005). Each essay was evaluated by three raters.…”
Section: Methodsmentioning
confidence: 99%
“…Reliability was assessed for triads of raters who evaluated 236 essays from students at the National Technical Institute for the Deaf (Schley & Albertini, 2005). Pearson correlations among pairs of raters were all above .81.…”
Section: Methodsmentioning
confidence: 99%
“…ISSN 1948-5476 2018 As an example, Strassman and Schirmer (2013) were interested in whether approaches to writing instruction with deaf students were similar to approaches used with hearing students. Prior research had found that the texts typically produced by deaf students are comprehensible but lacking in organization and supporting detail, choppy, and immature (e.g., Albertini & Schley, 2011;Antia, Reed, & Kreimeyer, 2005;Mayer, 2010;Paul, 2008) and that many deaf students are placed in writing remediation classes when they enter college (Schley & Albertini, 2005). These findings from the research on the writing development and achievement of deaf students suggested why it was important to determine whether research offered evidence for the effectiveness of instructional approaches that might improve these outcomes.…”
Section: Selecting the Research And Theoretical Literaturementioning
confidence: 99%
“…Although there is a small corpus of research suggesting that the linguistic proficiency of d/hh students may influence the unique characteristics found in their writing [13,18], there are only a few assessment options that specifically target written composition reported in the literature. Normreferenced standardized tests are often used to assess the writing skills of d/hh students [26]; however, the practice of evaluating the writing outcomes of d/hh students by these standardized assessments alone has been criticized, as they may not capture the unique strengths, weaknesses, and characteristics of d/hh students' writing [27].…”
Section: Introductionmentioning
confidence: 99%